Factors influencing the design of a multiparticulate dosing device - Lewis, Claire Jasmin (2018)
Paediatric specific medicines have become increasingly researched since the introduction of paediatric investigation plan requirements in 2007. Various dosage forms continue to be investigated for their appropriateness for children, including multiparticulates.